Strategi marketing untuk memasarkan pembiayaan haji guna meningkatkan jumlah nasabah pada bank muamalat kcp kepanjen - Kurniawati, Lina (Maliki Interdisciplinary Journal, 2025)
The maximum Islamic banking continues to grow rapidly, presenting competition in the financial sector that requires effective marketing strategies to attract customers. Bank Muamalat Indonesia, as a pioneer of Islamic banking in Indonesia, offers various superior products, including iB Hijrah Hajj Savings and Hajj Plus Financing, which make it easier for people to perform the hajj pilgrimage. This study highlights the marketing strategies of Bank Muamalat KCP Kepanjen in increasing the number of customers, such as collaboration with KBIH, digital promotion through the MuamalatDIN application, socialization to the sharia community, and a personal selling approach. The findings show that this strategy is effective in increasing customer interest, despite obstacles such as customer understanding and financial challenges. The solutions offered include education, motivation, and a hajj advance program. Regular evaluation is needed to overcome obstacles and ensure that the strategy runs optimally. This study emphasizes the importance of target-based marketing in strengthening the position of Islamic banks as a competitive and inclusive financial solution.